Barratt Impulsivity in Healthy Adults Is Associated with Higher Gray Matter Concentration in the Parietal Occipital Cortex that Represents Peripheral Visual Field - Ide, Jaime S.; Tung, Hsiang C.; Yang, Cheng-Ta; Tseng, Yuan-Chi; Li, Chiang-Shan R. (Frontiers in Human Neuroscience, 2017)
Impulsivity is a personality trait of clinical importance. Extant research focuses on fronto-striatal mechanisms of impulsivity and how executive functions are compromised in impulsive individuals. Imaging studies employing voxel based morphometry highlighted impulsivity-related changes in gray matter concentrations in a wide array of cerebral structures. In particular, whereas prefrontal cortical areas appear to show structural alterations in individuals with a neuropsychiatric condition, the findings are less than consistent in the healthy population. Here, in a sample (n=113) of young adults assessed for Barratt impulsivity, we controlled for age, gender, and alcohol use, and showed that higher impulsivity score is associated with increased gray matter volume in bilateral medial parietal and occipital cortices known to represent the peripheral visual field. When impulsivity components were assessed, we observed that this increase in parieto-occipital cortical volume is correlated with inattention and non-planning but not motor subscore. In a separate behavioral experiment of ten young adults, we demonstrated that impulsive individuals are more vulnerable to the influence of a distractor on target detection in an attention task. If replicated, this new finding suggests aberrant visual attention as a neural correlate of an impulsive personality trait in neurotypical individuals and needs to be reconciled with the literature that focuses on frontal dysfunctions.